Reinventing legal education : how clinical education is reforming the teaching and practice of law in Europe / edited by Alberto Alemanno, New York University School of Law, Lamin Khadar, DLA Piper. - Alemanno, Alberto; Khadar, Lamin (Cambridge University Press, 2018)
European legal teaching - historically formalistic, doctrinal, hierarchical, and passive - is coming under increasing pressure to reimagine itself as pragmatic, policy-aware, and action-oriented. Out of this context, a bottom-up movement of university law clinics appears to be emerging in Europe. Although intellectually indebted to the US model, the European variant reflects legal education and practice in Europe, specifically the multi-layered and multi-genetic legal landscape resulting from the Europeanization and internationalization of national legal systems, the globalization of European legal markets, and the growing demand for civic engagement in view of increasingly powerful supra-national institutions. Through the prism of clinical legal education, Reinventing Legal Education is the first attempt to gather scholarly and systematic reflections on the developments taking place in European legal teaching and practice. This groundbreaking book should be read by anyone interested in how clinical legal education is reinventing legal education in Europe.